Medical Imaging Data Security using Modified Honey Encryption Algorithm with Ant-Lion Optimization Technique - Prabhu, G. Jayahari; Perumal, B. (International Journal of Psychosocial Rehabilitation, 2020)
Security is the one of the significant thing for transmitting the restorative information. Since it contains some extra data of patients. Medical Imaging Data Security is a Necessary system for secure or safeguards the sensitive information and their related patient data and the information are put away and transmitted over the open system. Numerous cryptographic calculations are accessible, and they fall under symmetric, asymmetric and other procedures. To choose an algorithm for secure information correspondence, the algorithm should to give higher Privacy, security and better effectiveness. Here in medical imaging data, modified honey encryption uses DTE (Distribution Transforming Encoder). DTE encodes or decodes the message space using the Specified function and is used to scramble the restorative medical data. After that the Ant-Lion optimization is used to overhaul the keys. The presentation of the proposed methodology is assessed utilizing different parameters such as Entropy, Peak Signal to Noise ratio (PSNR), Correlation Coefficient (CC) and Mean Square error (MSE)